A Diagnostic Solution for Lupus Anticoagulant Testing in Patients Taking Direct Oral FXa Inhibitors Using DOAC Filter - Farkh, Carine; Ellouze, Syrine; Gounelle, Louis; Sad Houari, Mama; Duchemin, Jérôme; Proulle, Valérie; Fontenay, Michaela; Delavenne, Xavier; Jourdi, Georges (Frontiers in Medicine, 2021)
Background: Direct oral factor Xa (FXa) inhibitors interfere with lupus anticoagulant (LA) assays challenging antiphospholipid syndrome diagnosis in treated patients. We evaluated a new device, called DOAC Filter, and its usefulness in this setting. It is a single-use filtration cartridge in which FXa inhibitor compounds are trapped by non-covalent binding while plasma is filtered through a solid phase. Patient samples were analyzed before and after filtration: 38 rivaroxaban, 41 apixaban, and 68 none. Anticoagulant plasma concentrations were measured using specific anti-Xa assays and HPLC-MS/MS. LA testing was performed using dilute Russell Viper Venom Time (dRVVT) and Silica Clotting Time (SCT). Baseline median [min–max] concentrations were 64.8 [17.6; 311.4] for rivaroxaban and 92.1 ng/mL [37.1; 390.7] for apixaban (HPLC-MS/MS). They were significantly correlated with anti-Xa assay results (r = 0.98 and r = 0.94, respectively). dRVVT was positive in 92% rivaroxaban and 72% apixaban and SCT in 28 and 41% of samples, respectively. Post-filtration, median % of neutralization was 100% with rivaroxaban and apixaban concentrations of, respectively, <2 [<2–2.4] and <2 ng/mL [<2–9.6] using HPLC-MS/MS. No significant effect of DOAC Filter was observed on LA testing in controls (n = 31) and LA-positive (n = 37) non-anticoagulated samples. dRVVT and SCT remained positive in, respectively, 16 and 8% of rivaroxaban and 41 and 18% of apixaban samples. DOAC Filter would be an easy-to-use device allowing FXa inhibitor removal from plasma samples, limiting their interference with LA testing in treated patients.